Clinical and demographic features of ACL surgery cases: A retrospective descriptive study at H. Adam Malik General Hospital and Affiliated Hospitals (2017–2022) - Lubis, Abdurrahman Huzaifi; Siregar, Muhammad Hidayat; Albar, Husnul Fuad; Dibrata, R. Permana Yudha; Andriandi, Andriandi (Jurnal Prima Medika Sains, 2025)
Anterior cruciate ligament (ACL) injuries are among the most common knee injuries, particularly in physically active individuals. This retrospective descriptive study analyzed 118 patients who underwent ACL reconstruction at H. Adam Malik General Hospital and its affiliated centers between 2017 and 2022. Most patients were male (83.9%) with a mean age of 33.44 years, and 74.6% were engaged in occupations involving heavy manual labor. Contact injury was the predominant mechanism (75.4%), and complete ACL tears were identified in 65.3% of cases. The majority of surgeries were performed during the chronic phase (62.7%). The hamstring tendon autograft was the most frequently used graft type (78.0%), with graft diameters exceeding 8 mm in 66.1% of cases. Meniscal injuries were present in 41.5% of patients. All patients successfully returned to sport after more than six months of rehabilitation, and no postoperative infections or revision surgeries were reported. These findings characterize the demographic and clinical profile of ACL reconstruction patients in this setting and emphasize the importance of timely surgical intervention and structured rehabilitation to optimize functional outcomes.